2018
DOI: 10.1002/jclp.22651
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effectiveness of an intensive, 2‐week treatment program for military personnel and veterans with PTSD: Results of a pilot, open‐label, prospective cohort trial

Abstract: Daily administration of CPT is associated with significant reductions in PTSD and suicide ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 40 publications
5
35
0
Order By: Relevance
“…The relapse of PTSD symptoms at six month follow-up isalbeit undesirable not fully unexpected as it is in accordance with earlier findings among a similar sample of individuals undergoing the same treatment programme (Van Woudenberg et al, 2018), and has been observed in other treatment programmes with a massed format as well (e.g. Bryan et al, 2018). Possibly, there is a subgroup of patients with complex trauma histories who tend to show a slight relapse in the long term.…”
Section: Discussionsupporting
confidence: 90%
“…The relapse of PTSD symptoms at six month follow-up isalbeit undesirable not fully unexpected as it is in accordance with earlier findings among a similar sample of individuals undergoing the same treatment programme (Van Woudenberg et al, 2018), and has been observed in other treatment programmes with a massed format as well (e.g. Bryan et al, 2018). Possibly, there is a subgroup of patients with complex trauma histories who tend to show a slight relapse in the long term.…”
Section: Discussionsupporting
confidence: 90%
“…The results also support the practice of engaging individuals with SI in PTSD treatment rather than considering SI a contraindication for treatment. A significant proportion of the sample had remitted SI and decreased severity across treatment, consistent with prior literature (Bryan, Leifker, Rozek et al, 2018; Gradus et al, 2013; Stayton et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…These very treatments (e.g., CPT and PE) are those that have shown effects on SI (e.g., Stayton et al, 2019), so it could be particularly helpful to emphasize treatment matching to enhance outcomes. There could be modifications made for residential treatments to enhance effectiveness for this population including intensive daily format (e.g., Bryan et al, 2018) or variable length treatment (Galovski et al, 2012); these more intensive treatments could reduce length of stay while still providing an adequate dose of therapy. Length of stay, although not a significant factor related to SI course in this study, has important implications for veterans’ ability to participate in the treatment (e.g., logistical barriers), cost, and resources; as such, determining length of stays as well as doses of treatment associated with better outcomes should remain a priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive treatment programmes (ITPs) are being used increasingly to address posttraumatic stress disorder (PTSD) (Held, Bagley, Klassen, & Pollack, 2019a). In ITPs, evidence-based treatments for PTSD, such as Cognitive Processing Therapy (CPT), Prolonged Exposure (PE), Cognitive Therapy for PTSD (CT-PTSD), and Eye Movement Desensitization and Reprocessing (EMDR) are condensed into one (Ehlers et al, 2014;Held et al, 2019b;Hendriks, Kleine, Broekman, Hendriks, & van Minnen, 2018;Méndez, Nijdam, June ter Heide, van der Aa, & Olff, 2018), two (Bryan et al, 2018;Harvey et al, 2017), or three (Zalta et al, 2018) weeks with daily sessions rather than traditional weekly psychotherapy (Held et al, 2019a). Although still relatively new, intensive treatment delivery formats have shown robust reductions in patients' PTSD and depression symptoms in a matter of days (e.g., Beidel, Frueh, Neer, & Lejuez, 2017;Ehlers et al, 2014;Foa et al, 2018;Held et al, 2019b;Zalta et al, 2018).…”
Section: 针对退伍军人为期三周的基于认知加工疗法的强化Ptsd治疗计划之后 治疗获益的维持时间长达12个月mentioning
confidence: 99%